Urban Forms for a sustainable socio-metabolism – a survey on surveys from 20th century Portugal - Marat-Mendes, T.; d'Almeida, P. Bento; Borges, J.C. (12TH CITTA INTERNATIONAL CONFERENCE ON PLANNING RESEARCH, 2019)
Throughout the 20th century, a number of surveys conducted by architects, urban researchers, geographers and anthropologists collected extensive information on how Portuguese communities built their habitats, explored their territory and managed their nourishment, according to specific climatic, ecological and socio-economic conditions. Part of that material formed a valuable source of inspiration for architects and planners to rethink architectural design and urban planning, but also for researchers, whom have studied them in order to identify changes in architectural taste and spatial organization. A further potential of those surveys, we suggest, is the opportunity that they provide today to visually characterize patterns of change of human occupation and appropriation of space, and ultimately transitions of socio-metabolisms. Drawing from a selection of elements from 20th century architectural, geographical and urban surveys, we seek to portray key socio-metabolic changes which have occurred in the territory of the Lisbon Region, both in its rural and urban areas, while seeking to identify elements of urban form and patterns of land-use. Furthermore, we believe that 20th century surveys contain examples which suggest effective urban changes towards sustainability, and therefore are of strategic importance for the establishment of a future informed urban culture, also aware of the impacts on the metabolic function of the urban environment.